KONSEP PENDIDIKAN PSIKOLOGI RELIGIUSITAS REMAJA MUSLIM DALAM MOTIVASI BERAGAMA - Nirwana, Andri (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2020)
Islam outlines several important aspects in educating children, especially adolescents, to the path of Allah SWT. First, giving love and sufficient living needs. Teenagers in the initial ranks need enough affection than your mother so they don't feel emptiness in the soul. This responsibility must be carried out by the mother and father as well as possible. The Word of God which means QS. Ali-Imran: 14. The instincts of love that manifest in human beings should be nurtured as best as possible according to the will of Islamic law. In giving love to children, it is not enough for the mother and father just to provide material needs while their mental and emotional needs are not emphasized. Father and mother should spend time with their children to make love and get along with them. Father and mother also need to be a good friend to teenagers by providing opportunities to shed light on what problems they face. A divide that is not divided must be given when the teenager is pouring something or other resources to devote the problem that is being faced. A close relationship is very important between the mother father and teenage child. This method makes them not afraid to ask or tell stories if something happens to it. With this, the relationship between the child and his father's mother will be strengthened alongside their obedience and easy acceptance of their father's advice. A child who gets enough love and care from his father's mother will not disappoint his father's hopes. They will not look for happiness outside the home again, for example hanging out with naughty friends, smoking drugs, running away from home and so on because the happiness that is sought has been found at home. Second, provide religious education. Religious education is a duty of the mother and father. Without adequate religious education it is impossible to bear a child of morality and piety to God. Teaching and education should be prioritized related to religion because it is the best way to prevent people from being bad and bring them to glory